Optimal ratio of soil to guinea pig manure for optimum corn growth - Allera, Reynaldo M., Jr.; Cadiz, Geofe, Thesis adviser (Cebu City, Cebu Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Corn is one of the most economically significant cereal grains in the world. An increase in human population also means an increase for demand of corn. Farmers usually use inorganic fertilizers to increase their corn production. However, inorganic fertilizers can cause contaminations in the environment which can be detrimental to human, plant, and animal life. Animal manure can be used to create organic fertilizers that are a good substitute for inorganic fertilizers. Guinea pigs are an uncommonly used sources for animal manure. In this study, a greenhouse experiment in a completely randomized design was carried out to determine the optimal ratio of soil to guinea pig manure for optimum corn growth. Growth of corn plants under seven soil condition (pure soil, soil with commercial fertilizer, 15%, 30%, 45%, 60%, and 75% manure to soil mixture) were compared. Plant height, dry weight, total leaf area, specific leaf area, and root: shoot ratio were determined as measures of plant growth. The data was analyzed in R through one-way ANOVA to determine if there is a significant difference among groups, and Tukeô€œô€‚¶s HSD post hoc test to determine ô€šhich group has a significant difference. The plants grown in 15% manure had the tallest height but was only statistically different with those grown in 30% and 60% manure. The negative control group had the highest root: shoot ratio which was statistically different with the 15% and 30% manure group, suggesting it has a poorer soil quality. Including the mortality and survival rate of every conditions, the optimal ratio of soil to guinea pig manure seems to be around 15% and 30%. Manure proportion above 60% is detrimental to corn growth, with the proportion of 75% being fatal. Overall the guinea pig manure was an effective organic fertilizer at less than 30% in soil mixture.
Thesis (Bachelor of Science in Biology). University of the Philippines Cebu. June 2022